Une île en mutation - Thierry Simon (EchoGéo)
The Reunion island is engaged in a deep territorial change. This change results in particular in great work of infrastructures, mainly led in order to facilitate displacements, since always problematic. These works of width should however not occult, neither the structuring initiatives of less width (for example, the multiple zones of activities), nor the essential consistency and the effective setting of the multiple framings lawful whose island is equipped as regards land and regional planning.